INOVASI ALAT PENGUPAS KELAPA MUDA BAGI PELAKU USAHA MINUMAN SEGAR DI KOTA PADANG - Andre, Hanalde; Games, Donard; Hasan, Ashadi; Dewi, Risti Kurnia; Kurniawan, Miko; Susanto, Susanto; Sari, Ermana (LPPM Universitas Andalas, 2025)
The purpose of this activity is to design and develop an automatic young coconut peeling tool to improve production efficiency and the selling value of young coconut water-based beverage products. Young coconut products contain high nutritional value, such as water, carbohydrates, vitamins B and C, as well as essential minerals, making them a natural health drink with a broad market potential. However, in Padang City, the quality of packaging and the appearance of young coconut products are still considered low, which impacts their selling price. The methods used in this activity include the design phase of a tool based on a mechanical system with an electric motor, development of an automatic cutting mechanism from three sides (top, side, and bottom), as well as the integration of hot stamp technology for direct brand printing on the coconut surface. The prototype was tested to measure cutting precision, work efficiency, and the visual appeal of the final product. The results show that the tool is capable of producing young coconuts shaped like uniform, visually appealing white diamonds. In addition to improving production efficiency, the hot stamp technology also successfully strengthens the product’s brand identity. In conclusion, this automatic young coconut peeling tool provides an innovative solution for MSME actors to enhance product quality, added value, and competitiveness. This innovation also opens new market opportunities and contributes to strengthening the local economy based on superior tropical commodities.